EVALUASI IMPLEMENTASI PENGIMBASAN SISTEM PENJAMINAN MUTU INTERNAL (SPMI) SEKOLAH MODEL DI SEKOLAH DASAR: ANALISIS MENGGUNAKAN MODEL CIPP - Lestari, Neng Elis Seri; Sapriati, Amalia; Susandi, Ardi Dwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the implementation of the dissemination of the Internal Quality Assurance System (SPMI) in primary schools serving as model schools. The research method used is a descriptive qualitative approach, with data collected through in-depth interviews, observations, and document reviews. The analysis was carried out using the CIPP model (Context, Input, Process, Product) to identify supporting factors, constraints, and implementation achievements. The results show that, in the context aspect, the policies and commitment of the model schools form a strong foundation for the dissemination process. In the input aspect, support in terms of human resources, infrastructure, and funding is relatively adequate, although limitations still exist in recipient schools. The process aspect demonstrates a structured program implementation through training, mentoring, and continuous monitoring. In the product aspect, there is an increase in the recipient schools’ understanding of the SPMI concept, and most have successfully implemented the PPEPP cycle (Planning, Implementation, Evaluation, Control, and Improvement). However, program sustainability still requires strengthened supervision and collaboration between schools. This study recommends the development of more adaptive coaching strategies tailored to the conditions of recipient schools and the optimization of the role of school supervisors. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi pengimbasan Sistem Penjaminan Mutu Internal (SPMI) pada Sekolah Dasar yang menjadi sekolah model. Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan telaah dokumen. Analisis dilakukan menggunakan model CIPP (Context, Input, Process, Product) untuk mengidentifikasi faktor pendukung, kendala, serta capaian implementasi. Hasil penelitian menunjukkan bahwa pada aspek konteks, kebijakan dan komitmen pihak sekolah model menjadi dasar kuat pelaksanaan pengimbasan. Pada aspek input, dukungan sumber daya manusia, sarana-prasarana, dan pendanaan relatif memadai meskipun masih terdapat keterbatasan di sekolah imbas. Aspek proses memperlihatkan pelaksanaan program yang terstruktur melalui pelatihan, pendampingan, dan monitoring berkelanjutan. Pada aspek produk, terjadi peningkatan pemahaman sekolah imbas terhadap konsep SPMI dan sebagian besar berhasil menerapkan siklus PPEPP (Perencanaan, Pelaksanaan, Evaluasi, Pengendalian, dan Peningkatan). Namun, keberlanjutan program masih memerlukan penguatan supervisi dan kolaborasi antar sekolah. Penelitian ini merekomendasikan pengembangan strategi pembinaan yang lebih adaptif terhadap kondisi sekolah imbas serta optimalisasi peran pengawas sekolah.